2014
DOI: 10.4236/ajps.2014.525389
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fusarium Inoculation and Fungicide Application on Concentrations of Flavonoids (Apigenin, Kaempferol, Luteolin, Naringenin, Quercetin, Rutin, Vitexin) in Winter Wheat Cultivars

Abstract: Grain of 30 winter wheat cultivars was screened for the content of seven flavonoids (apigenin, kaempferol, luteolin, naringenin, quercetin, rutin, vitexin). In total, 90 samples were analyzed, belonging to three combinations: the control, samples inoculated with Fusarium culmorum, and samples inoculated with Fusarium culmorum and protected with fungicides (Prosaro, Topsin M). Analyzed flavonoids were detected in all tested samples. The highest concentrations were recorded for quercetin (512.9 mg/kg) and luteol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…In addition, few compounds of the flavanol (catechin and its derivatives), flavanone (naringenin), flavone (apigenin and vitexin derivatives) and anthocyanin (pelargonidin) classes were highlighted. These metabolomic data corroborate recent published studies that have indicated a significant induction of the expression of several genes involved in the biosynthetic pathway of flavonoids [ 47 ] and/or an increase in flavonol and flavanone concentrations [ 48 ] following wheat inoculation by F. graminearum. The main role ascribed to flavonoid in plant defense mechanisms results from their antioxidant properties [ 49 , 50 , 51 ], that allow them to reduce the production of and quench reactive oxygen species (ROS), generated by both the pathogen and the plant during infection.…”
Section: Chemical Groups Potentially Involved In Chemical Defense supporting
confidence: 90%
“…In addition, few compounds of the flavanol (catechin and its derivatives), flavanone (naringenin), flavone (apigenin and vitexin derivatives) and anthocyanin (pelargonidin) classes were highlighted. These metabolomic data corroborate recent published studies that have indicated a significant induction of the expression of several genes involved in the biosynthetic pathway of flavonoids [ 47 ] and/or an increase in flavonol and flavanone concentrations [ 48 ] following wheat inoculation by F. graminearum. The main role ascribed to flavonoid in plant defense mechanisms results from their antioxidant properties [ 49 , 50 , 51 ], that allow them to reduce the production of and quench reactive oxygen species (ROS), generated by both the pathogen and the plant during infection.…”
Section: Chemical Groups Potentially Involved In Chemical Defense supporting
confidence: 90%
“…Compounds were identified based on a comparison of retention times of the examined peak with that of the standard and by adding a specific amount of the standard to the tested sample and repeated analyses. The limit of detection was 1 mg/kg [36].…”
Section: Chromatographic Analysismentioning
confidence: 95%
“…Phenolic acids, flavonoids and ergosterol were analyzed using the ACQUITY UPLC H-Class System equipped with a PDA ek Detector (Waters Corporation, Milford, MA) as previously described (Bu sko et al, 2014;Gąsecka, Mleczek, Siwulski, & Niedzielski, 2016;Perkowski et al, 2008) with some modifications. Chromatographic separations were on an Acquity UPLC HSS T3 C 18 column (150 mm 3 2.1 mm, particle size 1.8 lm) (Waters, Ireland).…”
Section: Chromatographic Analysismentioning
confidence: 99%